How does climate exacerbate root causes of conflict in Somalia? A climate security pathway analysis - Sax, Niklas; Schapendonk, Frans; Kenduiywo, Benson; Villa, Victor; Craparo, Alessandro; Benzid, Rym; Nunow, Abdimajid; Pacillo, Grazia (2024)
This factsheet gives answers on how climate exacerbates root causes of conflict in Somalia using a pathway analysis. Four main pathways are identified, namely, 1) resource access and availability, which illustrates how climate impacts affect natural resource availability, leading to different forms of resource-related conflicts; 2) livelihood and food insecurity, which examines how climate change impacts agricultural production and livelihoods in Somalia; 3) disaster and conflict displacement, which delves into the compounding effects of climate-induced and conflict-driven displacement on insecurity dynamics in Somalia; and 4) fragility, conflict and exploitation, which examines how climate change exacerbates existing socioeconomic inequalities, political representation, power dynamics and grievances within the country.